Estimasi nilai pasar wajar PT Bristol-Myer Squibb Indonesia Tbk. pada saat diakuisisi oleh Taisho Pharmaceutical Co., Ltd - ADLIANSYAH, Gusti Fahmi ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The purpose of this research is to estimate the equity fair market value of PT Bristol-Myer Squibb Indonesia Tbk when acquired by Taisho Pharmaceutical Co.,Ltd using Discounted Cash Flow Method and Relative Valuation Method. The data use in the research consist of its financial report (2004-2008), comparable company’s report, risk free rate, and another supporting data. The analysis used is Discounted Cash Flow Method which go with following step: sale projection analysis, financial statement projection, free cash flow to equity projection, discount rate determination and value estimation. Relative valuation method was started by determining similar company in the same field of industry, followed by choosing and determining the multiple that be used to converse book value on relevant variable of PT Bristol-Myer Squibb Indonesia Tbk to be estimation of fair market value. Multiple that used in this research is Price Earning Ratio (PER). The result from this research by using Discounted Cash Flow Method is Rp143,609.00 per share and result by using Relative Valuation Method is Rp145,157.00 per share. Reconsiliation result from two method obtained the fair market value of PT Bristol-Myer Squibb Indonesia Tbk is from Rp143,609.00 until Rp Rp145,157.00 per share.